Saliva sebagai Media Diagnosis untuk Deteksi Keganasan - Dian Yosi Arinawati; Aprilinda Widyawati (Fakultas Kedokteran Gigi Universitas Jember, 2022)
Human saliva is a potential diagnostic fluid where most of changes in the body can be reflected in saliva and it considered a